Capital Flows at Risk : Taming the Ebbs and Flows - Gelos, R. (IMF Working Papers; Working Paper ;, 2019)
The volatility of capital flows to emerging markets continues to pose challenges to policymakers. In this paper, we propose a new framework to answer critical policy questions: What policies and policy frameworks are most effective in dampening sharp capital flow movements in response to global shocks? What are the near- versus medium-term trade-offs of different policies? We tackle these questions using a quantile regression framework to predict the entire future probability distribution of capital flows to emerging markets, based on current domestic structural characteristics, policies, and global financial conditions. This new approach allows policymakers to quantify capital flows risks and evaluate policy tools to mitigate them, thus building the foundation of a risk management framework for capital flows.